Decoupling the rotation of stars and gas – II. The link between black hole activity and simulated IFU kinematics in IllustrisTNG. Issue 4 (30th May 2020) - Duckworth, Christopher; Starkenburg, Tjitske K; Genel, Shy; Davis, Timothy A; Habouzit, Mélanie; Kraljic, Katarina; Tojeiro, Rita
ABSTRACT: We study the relationship between supermassive black hole (BH) feedback, BH luminosity, and the kinematics of stars and gas for galaxies in IllustrisTNG. We use galaxies with mock MaNGA observations to identify kinematic misalignment at z = 0 (difference in rotation of stars and gas), for which we follow the evolutionary history of BH activity and gas properties over the last 8 Gyr. Misaligned low-mass galaxies ($\mathrm{ M_{stel} \lt 10^{10.2}\, M_{\odot }}$ ) typically have boosted BH luminosity and BH growth, and have had more energy injected by BHs into the gas over the last 8 Gyr in comparison to low-mass aligned galaxies. These properties likely lead to outflows and gas removal, in agreement with active low mass galaxies in observations. Splitting on BH luminosity at z = 0 produces consistent distributions of kinematic misalignment at z = 0; however, splitting on the maximum BH luminosity over the last 8 Gyr produces statistically significant different distributions. While instantaneous correlation at z = 0 is difficult due to misalignment persisting on longer time-scales, the relationship between BH activity and misalignment is clear. High-mass quenched galaxies ($\mathrm{ M_{stel} \gt 10^{10.2}\, M_{\odot }}$ ) with misalignment typically have similar BH luminosities, show lower gas fractions, and have typically lower gas phase metallicity over the last 8 Gyr in comparison to the high mass aligned.